(untitled) (AYUSHDHARA, 2024)
Traditional healers use Syzygium cumini bark to treat inflammation. The main aim of this work is to formulate an emulgel containing extract of Syzigium cumini. Syzygium cumini bark was extracted using hydro-alcoholic solvent. Phytochemical evaluation of extract was done. In-vitro anti-inflammatory activity of the extract was evaluated. 4 batches of emulgel were formulated by varying the concentrations of the gelling agents. The emulgel was evaluated for pH, spreadability, viscosity, consistency, appearance, color, washability and appearance. Best results were shown by F2 formulation. Stability studies if F2 formulation was carried. The formulation was found to be stable. It was considered better for treatment of skin inflammation. The proposed research work concludes that the newly formulated herbal emulgel loaded with extract of Syzygium cumini can be used in future for anti-inflammatory effect.